Eksistensi Pendidikan Agama: (Studi Tentang Realitas Sosial dan Status Guru Dalam Pendidikan Agama) - Raikhan, Raikhan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
There is an exaggerated but realistic worry that the author felt before writing this paper, after several times hearing and discussing with some fellow practitioners of education about a phrase that says